Studi Literatur tentang Pengaruh Media Flashcard terhadap Kemampuan Numerasi Siswa Sekolah Dasar - Fauziah, Naila; Amri, Mira Amelia; Putra, Adi (Papanda, 2025)
This literature study aims to determine the effect of flashcard learning media in improving elementary school students' numeracy skills. The method used is a literature review with a qualitative approach, conducted through the exploration of various reputable electronic databases such as Google Scholar, ResearchGate, and Portal Garuda. During the data collection process, the researcher identified and gathered relevant articles based on specific inclusion and exclusion criteria. The selected articles are recent studies published within the last five years, from 2019 to 2024, in both Indonesian and English. The results of the study indicate that the use of flashcard media significantly improves the understanding of numeracy concepts, learning motivation, and active involvement of students during the learning process. Flashcards that are visual, simple, and easy to operate have proven effective in helping students understand the concept of numbers, basic operations, and problem solving in a concrete and real way. In addition, the use of flashcards can also improve the interactive and enjoyable classroom atmosphere, and strengthen the relationship between teachers and students. However, there are several obstacles such as the lack of teacher training in designing innovative media, and the limited variety of media used. Therefore, it is recommended that the development of flashcard media be carried out continuously with more diverse variations and adjusted to students' needs, and followed by training for teachers so that the use of this media can be optimized. This study makes an important contribution to improving the quality of numeracy learning at the elementary education level.